KCNJ11 activating mutations are associated with developmental delay, epilepsy and neonatal diabetes syndrome and other neurological features. - Gloyn, A; Diatloff-Zito, C; Edghill, E; Bellanné-Chantelot, C; Nivot, S; Coutant, R; Ellard, S; Hattersley, A; Robert, J (2006)
Heterozygous activating mutations in the gene encoding for the ATP-sensitive potassium channel subunit Kir6.2 (KCNJ11) have recently been shown to be a common cause of permanent neonatal diabetes. Kir6.2 is expressed in muscle, neuron and brain as well as the pancreatic beta-cell, so patients with KCNJ11 mutations could have a neurological phenotype in addition to their diabetes. It is proposed that some patients with KCNJ11 mutations have neurological features that are part of a discrete neurological syndrome termed developmental Delay, Epilepsy and Neonatal Diabetes (DEND), but there are also neurological consequences of chronic or acute diabetes. We identified KCNJ11 mutations in four of 10 probands with permanent neonatal diabetes and one affected parent; this included the novel C166F mutation and the previously described V59M and R201H. Four of the five patients with mutations had neurological features: the patient with the C166F mutation had marked developmental delay, severe generalised epilepsy, hypotonia and muscle weakness; mild developmental delay was present in the patient with the V59M mutation; one patient with the R201H mutation had acute and chronic neurological consequences of cerebral oedema and another had diabetic neuropathy from chronic hyperglycaemia. In conclusion, the clinical features in these patients support the existence of a discrete neurological syndrome with KCNJ11 mutations. The severe DEND syndrome was seen with the novel C166F mutation and mild developmental delay with the V59M mutation. These features differ markedly from the neurological consequences of acute or chronic diabetes.